Pengaruh Fee Audit dan Rotasi Auditor terhadap Kualitas Audit pada Perusahaan Manufaktur di BEI Tahun 2019-2022 - Cahyono, Efri; Suyono, Eko; Lestari, Puji (https://jurnal.binamandiri.ac.id/, 2024)
The auditor performs tasks by adhering to applicable audit standards and the code of ethics for public accountants. In addition, auditors at public accounting firms play a role in assessing the fairness of a company's financial statements in all aspects, including recognition, measurement, reporting, and disclosure. The aim of this study is to analyze the effect of audit fees on audit quality in manufacturing companies and to analyze the effect of auditor rotation on audit quality in manufacturing companies. The subject of the research is food and beverage sub-sector manufacturing companies listed on the Indonesia Stock Exchange (IDX) from 2019 to 2022, totaling 59 companies per year. The sample represents a portion of the population that serves as the subject of the research. In this study, the entire population will be used as the sample, amounting to 59 companies each year. Since the research covers the period from 2019 to 2022 (4 years), the total sample for this study is 236 companies. This research uses secondary data, specifically from the financial statements of companies from 2019 to 2022. Descriptive statistics using SPSS will be applied to test the data, and multiple linear regression analysis will be used to evaluate the hypotheses. The results of this study indicate that audit fees have no effect on audit quality, whereas auditor rotation does have an effect on audit quality.